1995
DOI: 10.2214/ajr.165.4.7676988
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of partial tears of the anterior cruciate ligament of the knee: value of MR imaging.

Abstract: OBJECTIVE.The purpose of our study was to assess the ability of MR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(96 citation statements)
references
References 0 publications
2
91
0
3
Order By: Relevance
“…While MRI can be a useful adjunct in making an accurate diagnosis with a complete ACL tear, reports have shown poor sensitivity of MRI in detecting partial ACL tears [16,17] (Fig. 2).…”
Section: Examinationmentioning
confidence: 99%
“…While MRI can be a useful adjunct in making an accurate diagnosis with a complete ACL tear, reports have shown poor sensitivity of MRI in detecting partial ACL tears [16,17] (Fig. 2).…”
Section: Examinationmentioning
confidence: 99%
“…Although some studies have reported that MRI is sensitive and specific for diagnosing complete ACL rupture [7,20,26,28], other studies reported limited diagnostic value of MRI for distinguishing between partial and complete ACL tears [10,[27][28][29]. Furthermore, clear discrimination of the two bundles of ACL can sometimes be difficult [22].…”
Section: Discussionmentioning
confidence: 99%
“…These three categories were determined based on previously reported MRI criteria of ACL injury (Figs. 5-7) [18,[27][28][29]. Completely torn was defined as a failure to visualize the ACL.…”
Section: Mri Protocol and Interpretation (77 Knees)mentioning
confidence: 99%
See 1 more Smart Citation
“…While acute complete ACL tears generally present no diagnostic challenge with MRI, partial-thickness tears can be more problematic [46,47]. Partial-thickness tears may be seen on MRI as mild bowing of the ligament [46].…”
Section: Anterior Cruciate Ligamentmentioning
confidence: 99%